Hydropower - Breeze, Paul A. (London : Academic Press, 2018)
Annotation 'Hydropower' provides a complete discussion of the most up-to-date considerations of this method of creating renewable energy. After introducing the method's history, the author explores various considerations for engineers, planners and managers who need to determine the best placement and size of a plant. The book then presents various types of hydropower systems, such as Run-of-River Schemes and various types of Dam and Turbines, also considering the important economic, environmental and geological impacts of each. Those involved in the planning, design and management of hydropower systems, such as engineers, researchers, managers and policymakers will find this book a very valuable and insightful resource.
Sedimentation and Downstream Effects; Greenhouse Gases; Interregional Effects; 10. The Cost of Electricity From Hydropower Plants; Levelized Cost of Electricity; Capital Cost of Hydropower Plants; LCOE From Hydropower Plants; Index; Back Cover.
Online resource; title from PDF title page (EBSCO, viewed April 4, 2018).
Includes index.
Keywords: Water-power.; Economic surveys; Hydroelectric power plants; Power Plants; Enqu etes economiques; Centrales hydro electriques; hydroelectric power plants; BUSINESS & ECONOMICS -- Real Estate -- General; Economic surveys; Hydroelectric power plants; Water-power.